Maneuvering between two interests: Islam and Indonesia’s global identity the Joko Widodo Administration in 2014-2019 - Utomo, Ario Bimo (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This article discusses how the leadership of the first era of Indonesian President Joko Widodo (2014-2019) managed Islam as one aspect of his country’s identity in the global arena. The authors argue that two things influenced the image of Indonesian Islam in the Widodo era. First is the domestic pressure to reclaim the trust of Islamic political groups. Second is a global interest to maintain the status quo as a country with moderate Islamic characteristics that is also active in pursuing world peace. To do this, the authors use a two-level game point of view that sees the constellation of domestic politics and then relates it to how theWidodo government carries out its foreign diplomatic strategy. This article finds that the Widodo administration in the first era could balance the interests of creating an image of a friendly government to Islamic groups. On the other hand, it can also fulfil its commitment to engage in diplomacy as a middle power through strategies dominated by results oriented bilateralism.